ACCOUNTABILITY OF THE REGIONAL REPRESENTATIVE COUNCIL'S SUPERVISION FUNCTION IN THE BUDGET AND REGIONAL EXPENDITURE REVENUE OF PARIGI MOUTONG DISTRICT - Santrillah, Amelia; Waris, Irwan; Kurnia, Intam (Penerbit Lafadz Jaya, 2024)
This study aims to determine and analyze the accountability of the supervisory function of the Regional People's Representative Council for the implementation of the Parigi Moutong Regency APBD in realizing good governance and to find out the obstacles and solutions faced by the DPRD in the implementation of the supervisory function in the implementation of the Parigi Moutong Regency APBD. The type of research used is qualitative research. The determination of informants is carried out in a purposive way. The types of data used are primary data and secondary data. Data collection techniques, carried out through observation, interviews, documentation. The data analysis used is the interactive analysis model of Miles and Huberman in Hardinsyah (2015), namely the process of data collection, data condensation, data display, and conclusion drawing (verification). The theory used in this study is the theory proposed by Syahruddin Rasul (2002), where in assessing an accountability there are five dimensions of accountability, namely (1) aspects of legal accountability and honesty, (2) aspects of managerial accountability, (3) aspects of program accountability, (4) aspects of policy accountability and finally (5) aspects of financial accountability. The results showed that the DPRD Parigi Moutong in carrying out the supervisory function of the Regional Budget still has several shortcomings, namely the complexity of most DPRDs that must be improved, DPRD initiatives that are lacking related to the preparation of benchmark material documents in the implementation of supervisory activities, less than optimal communication between the DPRD and Regional Government TAPD, and the interests of the DPRD which are often the main focus of the DPRD that ignores the interests of the people as a whole.